Malay computer-aided speech therapy using audiofingerprint - Mat Zin, Nor Azan; Banihashem, Seyed Yashar; Mohd Daud, Salwani; Sheikh Abdullah, Siti Norul Huda; Iida, Hiroyuki (2015)
User-Centered Design (UCD) is a term to describe design processes which focus on designing for and involving users in the design of applications.The implementation of UCD in the game design process can enhance the user experience especially for special needs users such as motor-impaired users (MIU).This is very important, since the user experience will eventually be a significant element in the computer game’s success.The main objective of this study is to investigate UCD as a methodological tool to design and develop enjoyable games for MIU. The findings of the study showed users’ feedback on game design for MIU while applying UCD methods to game improvement and evaluation. Hopefully, the results of the study will emphasize the need for developing enjoyable game designs for MIU.